2003
DOI: 10.1046/j.1365-2745.2003.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass tree mortality leads to mangrove peat collapse at Bay Islands, Honduras after Hurricane Mitch

Abstract: Summary 1We measured sediment elevation and accretion dynamics in mangrove forests on the islands of Guanaja and Roatan, Honduras, impacted by Hurricane Mitch in 1998 to determine if collapse of underlying peat was occurring as a result of mass tree mortality. Little is known about the balance between production and decomposition of soil organic matter in the maintenance of sediment elevation of mangrove forests with biogenic soils. 2 Sediment elevation change measured with the rod surface elevation table from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
201
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(226 citation statements)
references
References 31 publications
15
201
0
2
Order By: Relevance
“…The RSET method has been useful not only for documenting trends in surface elevation change in specific wetlands 40 , but also for comparing rates of elevation change among hydrogeomorphic zones within a site (for example, a delta 41 ), differentiating between sites dominated by surface processes 40 versus subsurface processes 14 , documenting high variability in sediment deposition from singular storm events 44 , capturing rapid peat collapse from small-scale (for example, lightning strikes) and large-scale (for example, hurricanes) disturbances 45,46 , measuring the effects of elevated atmospheric CO 2 concentrations on surface elevation change 47 , and disentangling complex interactions among herbivory, biomass production and surface elevation change 48 . RSET data have also contributed to more applied research assessing the impacts of management practices on site-specific vulnerability to SLR, such as prescribed burning 49 , sedimentation from point-source coastal management interventions 50 , water diversion 51 , fence construction to enhance sediment deposition 52 and thin-layer deposition of dredged sediment 53 .…”
Section: Simple Affordable High-precision Datamentioning
confidence: 99%
“…The RSET method has been useful not only for documenting trends in surface elevation change in specific wetlands 40 , but also for comparing rates of elevation change among hydrogeomorphic zones within a site (for example, a delta 41 ), differentiating between sites dominated by surface processes 40 versus subsurface processes 14 , documenting high variability in sediment deposition from singular storm events 44 , capturing rapid peat collapse from small-scale (for example, lightning strikes) and large-scale (for example, hurricanes) disturbances 45,46 , measuring the effects of elevated atmospheric CO 2 concentrations on surface elevation change 47 , and disentangling complex interactions among herbivory, biomass production and surface elevation change 48 . RSET data have also contributed to more applied research assessing the impacts of management practices on site-specific vulnerability to SLR, such as prescribed burning 49 , sedimentation from point-source coastal management interventions 50 , water diversion 51 , fence construction to enhance sediment deposition 52 and thin-layer deposition of dredged sediment 53 .…”
Section: Simple Affordable High-precision Datamentioning
confidence: 99%
“…Cyclones in the Bay of Bengal show a similar average 29-year periodicity (Singh et al 2000). Hurricanes and cyclones can certainly cause large scale destruction of mangrove forests; Cahoon et al (2003) cite papers showing that ''powerful storms have caused mass mortality of at least 10 Caribbean mangrove forests during the past 50 years.'' However, there is evidence that mangroves are more resistant and resilient compared with other forest types when exposed to the same storms.…”
Section: Windmentioning
confidence: 99%
“…Changes in storm intensity can also affect vegetated coastal wetlands. Cahoon et al (2003) analysed the elevation responses from a variety of hurricane-influenced coastal settings and found that a storm can simultaneously influence both surface and subsurface soil processes, but with much variability. Saltmarshes (halophytic grasses, sedges, rushes and succulents) are common features of temperate depositional coastlines.…”
Section: Mangroves Saltmarshes and Sea Grassesmentioning
confidence: 99%
“…Nevertheless, it seems highly likely that similar principles are in operation and that the sedimentary response of the shoreline is a function of both the availability of sediment (Walsh and Nittrouer, 2004) and the ability of the organic production by mangroves themselves to fill accommodation space provided by sea-level rise (Simas et al, 2001). Mangroves are able to produce root material that builds up the substrate beneath them (Middleton and McKee, 2001;Jennerjahn and Ittekkot, 2002), but collapse of peat occurs rapidly in the absence of new root growth, as observed after Hurricane Mitch (Cahoon et al, 2003) and after lightning strikes (Sherman et al, 2000). Groundwater levels play an important role in the elevation of mangrove soils by processes affecting soil shrink and swell.…”
Section: Mangroves Saltmarshes and Sea Grassesmentioning
confidence: 99%
See 1 more Smart Citation